Isolasi dan Identifikasi Agrobacterium tumefaciens dari Tanaman Wortel (Daucus carota L.) - MANALU, YOLANDA HASSIAN; WIRAWAN, I GEDE PUTU; SUSRAMA, I GEDE KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Isolation and Identification of Agrobacterium tumefaciens from  Carrots ( Daucus carota L.) Agrobacterium tumefaciens is a plant pathogenic bacterium that is widely used as a vector for inserting foreign genes into a plant chromosome to produce a transgenic plant. This bacterium cause a disease namely crown gall in dicotyledonous plants. This study is aim to isolate A. tumefaciens from local carrot ( Daucus carota L.) by using some method such as selection media, characterization of the bacteria, and confirm by Koch’s postulates. The result of this study determined that carrot’s root taken from Bedugul area which showed crown gall symptom, an A. tumefaciens due to its characteristics e.g. shape of colonies, color, and growth of the bacteria in AB minimal medium that was a specific for A. tumefaciens .  By using the Koch’s postulates test showed that the isolated caused convex gall on the surface of carrot slice. DNA of isolated bacterium successfully electroforeted through agarose gel electrophoresis.  These results showed that the bacteria associated with carrot was A. tumefaciens. Keywords : A. tumefaciens, AB medium, Carrot, LB medium, Crown gall